Cellobiose Dehydrogenase Aryl Diazonium Modified Single Walled Carbon Nanotubes: Enhanced Direct Electron Transfer through a Positively Charged Surface - Tasca, Federico (American Chemical Society, 2011)
[Image: see text] One of the challenges in the field of biosensors and biofuel cells is to establish a highly efficient electron transfer rate between the active site of redox enzymes and electrodes to fully access the catalytic potential of the biocatalyst and achieve high current densities. We report on very efficient direct electron transfer (DET) between cellobiose dehydrogenase (CDH) from Phanerochaete sordida (PsCDH) and surface modified single walled carbon nanotubes (SWCNT). Sonicated SWCNTs were adsorbed on the top of glassy carbon electrodes and modified with aryl diazonium salts generated in situ from p-aminobenzoic acid and p-phenylenediamine, thus featuring at acidic pH (3.5 and 4.5) negative or positive surface charges. After adsorption of PsCDH, both electrode types showed excellent long-term stability and very efficient DET. The modified electrode presenting p-aminophenyl groups produced a DET current density of 500 μA cm(−2) at 200 mV vs normal hydrogen reference electrode (NHE) in a 5 mM lactose solution buffered at pH 3.5. This is the highest reported DET value so far using a CDH modified electrode and comes close to electrodes using mediated electron transfer. Moreover, the onset of the electrocatalytic current for lactose oxidation started at 70 mV vs NHE, a potential which is 50 mV lower compared to when unmodified SWCNTs were used. This effect potentially reduces the interference by oxidizable matrix components in biosensors and increases the open circuit potential in biofuel cells. The stability of the electrode was greatly increased compared with unmodified but cross-linked SWCNTs electrodes and lost only 15% of the initial current after 50 h of constant potential scanning.